EXPLORING PROBLEM-SOLVING SKILLS PROFILES OF PRE-SERVICE MATHEMATICS TEACHERS THROUGH POLYA’S FOUR STAGES: Riau, Indonesia - Wahyuni, Reni; Wahyuni, Astri; Angraini, Lilis Marina; Sthephani, Aulia (Universitas Muhammadiyah Bengkulu, 2025)
Mathematical problem-solving skills are an essential competence for pre-service mathematics teachers, as they are expected to cultivate these skills in their future students. This study aims to describe the problem-solving profiles of pre-service mathematics teachers using Polya’s four stages as an analytical lens. A qualitative case study approach was employed to examine the cognitive processes demonstrated by pre-service teachers while solving mathematical problems. The findings reveal diverse problem-solving profiles, including conceptual understanding shaped by prior experience, logical reasoning used to interpret problem conditions, and the ability to represent problems through mathematical models. These profiles underscore the need for dedicated coursework that enhances mathematical problem-solving skills within mathematics education programs. The study provides insights into the variation of problem-solving profiles and offers implications for curriculum development in the mathematics education department. Keywords: Mathematical problem-solving skills, pre-service mathematics teachers, Polya’s profile, qualitative research